h - Tuamsuk, Kulthida; Jatowt, Adam.; Rasmussen, Edie.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 16th International Conference on Asia-Pacific Digital Libraries, ICADL 2014, held in Chiang Mai, Thailand, in November 2014. The 20 full papers, 19 short papers and 9 poster papers presented were carefully reviewed and selected from 141 submissions. The papers are organized in topical sections on digital preservation and archiving; digital repositories and tools; scholarly documents repositories; metadata and ontologies; linked data and knowledge sharing; digital books and e-books; digital libraries usage and applications; data management and classification; information retrieval and search methods; user skills and experiences.
Digital preservation and archiving -- Digital repositories and tools -- Scholarly documents repositories -- Metadata and ontologies -- Linked data and knowledge sharing -- Digital books and e-books -- Digital libraries usage and applications -- Data management and classification -- Information retrieval and search methods -- User skills and experiences.
Keywords: Computer science; Database management; Information storage and retrieval; Text processing (Computer science).; Computer Science; Information Storage and Retrieval; Document Preparation and Text Processing; Database Management; Information Systems Applications (incl. Internet).; Electronic books